Gambaran Kepatuhan Terhadap Penggunaan Alat Pelindung Diri (APD) Pada Pekerja Bengkel Las di Kecamatan Medan Tembung - Nur Asiyah Siregar; Susilawati Susilawati (Journal of Educational Innovation and Public Health, 2024)
Since welding workshops are an unofficial industry, there is still a lack of effective implementation of occupational safety and health regulations in this field. Welders often experience eye hazards such as sparks, foreign objects, infrared and UV radiation. The purpose of this study is to describe how well welding workshop workers in Medan Tembung District comply with the use of personal protective equipment (PPE). This study uses a quantitative descriptive method. The results of data analysis for the Alpha Cronbach questionnaire trial in this study showed that the data met the requirements with a score of 0.928. Up to 55 welding workshop employees from all welding workshops in Medan Tembung District, Medan City participated in the total sampling of this study. After the descriptive analysis, the data is displayed as a frequency distribution. According to the results of the study, of the 55 welding workshop employees who participated in the survey, 50.9% had a low level of knowledge. The majority of respondents (80%) have a negative attitude towards the use of personal protective equipment (PPE), and more than half (58.2%) do not use PPE in the workplace. The results of the data analysis show that the majority of employees ignore the need to wear personal protective equipment (PPE) in the workplace because they do not know it or have a negative attitude towards it. Thus, this study suggests that welding businesses need to provide complete personal protective equipment, and also educate on the importance of using PPE and the Government also needs to increase supervision for small and medium enterprises, especially in welding workshops related to occupational health and safety.